Mesophase in melt-spun poly(ϵ-caprolactone) filaments: Structure–mechanical property relationship. (7th October 2020) - Selli, F.; Erdoğan, U.H.; Hufenus, R.; Perret, E.
Abstract: Fine poly(ϵ-caprolactone) (PCL) filaments (diameter: 59–92 μm) were successfully melt-spun with modified drawing setups to prevent draw instabilities. Depending on the production parameters, different mechanical properties were obtained (tensile strength: 302–456 MPa, elongation at break: 69–88%). These variations are related to subtle structural differences, which we have analyzed with wide-angle x-ray diffraction (WAXD) and small-angle x-ray scattering (SAXS). SAXS was used to determine crystal widths and the spacing between crystals along the filament axis. Additionally, 2D WAXD patterns were simulated and WAXD profiles were fitted. The detailed 2D WAXD analysis revealed that a highly-oriented non-crystalline mesophase is present in drawn PCL filaments, which is most-likely situated in-between PCL crystals. A large amount of this mesophase (>16%), combined with high crystalline orientation and perfect crystals, led to higher tensile strength values. We also confirmed that PCL chains pack with non-planar chain conformations in the unit cell. Graphical abstract: Image 1 Highlights : Upscalable melt-spinning procedure for fine poly(ϵ-caprolactone) filaments. Structure-mechanical property relationship in PCL filaments. 2D WAXD simulations and fits reveal the existence of a mesophase. Structural analysis with SAXS: crystal sizes and long spacing.